Investigating the Role of Glutamate in Obsessive-Compulsive Disorder: Current Perspectives - Karthik S (Dove Medical Press, 2020)
Sheshachala Karthik,* Lavanya P Sharma,* Janardhanan C Narayanaswamy OCD Clinic, Department of Psychiatry, National Institute of Mental Health and Neurosciences (NIMHANS), Bangalore 560029, India*These authors contributed equally to this workCorrespondence: Janardhanan C NarayanaswamyOCD Clinic, Department of Psychiatry, National Institute of Mental Health and Neurosciences (NIMHANS), Bangalore 560029, IndiaTel +91 8026995250Email jcn.nimhans@gmail.comAbstract: Glutamate is a ubiquitous excitatory neurotransmitter, which is involved in normal physiology, a variety of central nervous system (CNS) functions, including excitotoxicity and neuronal migration. It is implicated in the pathogenesis of various neuropsychiatric disorders including epilepsy, Parkinson’s disease, Alzheimer’s dementia, schizophrenia and obsessive compulsive disorder (OCD). Over the years, a growing body of evidence has helped researchers understand the mechanisms underlying glutamatergic involvement in the pathogenesis of these disorders. In this review, we attempt to elucidate the role of glutamate in OCD, which is a chronic psychiatric condition with significant morbidity. This article provides current perspectives on the role played by glutamate in the pathogenesis, clinical symptoms and treatment response in OCD, a critical analysis of existing and emerging evidence, both clinical and preclinical, followed by a summary and future directions.Keywords: glutamate, NMDA receptor, OCD, striatum, memantine, lamotrigine